Hubungan Antara Pola Konsumsi Makanan Cepat Saji dengan Obesitas pada Remaja di Kota Praya - Juhaini, Juhaini; Saputra, Yogi (Gema Cendekia Institute, 2025)
Background: The increasing prevalence of obesity in adolescents is a worrying public health problem, especially in urban and semi-urban areas. One of the main risk factors suspected to contribute is the consumption pattern of fast food that is high in calories and low in nutritional value. This study aims to analyze the relationship between fast food consumption patterns and the incidence of obesity in adolescents in Praya City, Central Lombok. Methods: This study used a quantitative approach with a cross-sectional study design. A sample of 150 adolescents aged 13–18 years was selected purposively from several high schools in Praya City. Data were collected through questionnaires regarding the frequency and type of fast food consumed, as well as body mass index (BMI) measurements to determine obesity status. Data analysis was performed using the chi-square test and logistic regression. Results: The results of the analysis showed a significant relationship between the frequency of fast food consumption and the incidence of obesity in adolescents (p < 0.05). Adolescents who consume fast food more than three times a week have a 2.8 times higher risk of obesity compared to those who rarely consume it. Conclusion: There is a significant relationship between fast food consumption patterns and the incidence of obesity in adolescents in Praya City. Nutrition education and promotion of healthy eating patterns need to be improved to reduce the risk of obesity among adolescents.